Plasma alkylresorcinols, biomarkers of whole-grain wheat and rye intake, and incidence of colorectal cancer - Kyrø, Cecilie; Olsen, Anja; Landberg, Rikard; Skeie, Guri; Loft, Steffen; Åman, Per; Leenders, Max; Dik, Vincent K.; Siersema, Peter D.; Pischon, Tobias; Christensen, Jane; Overvad, Kim; et al. (Oxford University Press, 2014)
BackgroundFew studies have investigated the association between whole-grain intake and colorectal cancer. Because whole-grain intake estimation might be prone to measurement errors, more objective measures (eg, biomarkers) could assist in investigating such associations.MethodsThe association between alkylresorcinols, biomarkers of whole-grain rye and wheat intake, and colorectal cancer incidence were investigated using prediagnostic plasma samples from colorectal cancer case patients and matched control subjects nested within the European Prospective Investigation into Cancer and Nutrition. We included 1372 incident colorectal cancer case patients and 1372 individual matched control subjects and calculated the incidence rate ratios (IRRs) for overall and anatomical subsites of colorectal cancer using conditional logistic regression adjusted for potential confounders. Regional differences (Scandinavia, the Mediterranean, Central Europe) were also explored.ResultsHigh plasma total alkylresorcinol concentration was associated with lower incidence of distal colon cancer; the adjusted incidence rate ratio of distal colon cancer for the highest vs lowest quartile of plasma total alkylresorcinols was 0.48 (95% confidence interval [CI] = 0.28 to 0.83). An inverse association between plasma total alkylresorcinol concentrations and colon cancer was found for Scandinavian participants (IRR per doubling = 0.83; 95% CI = 0.70 to 0.98). However, plasma total alkylresorcinol concentrations were not associated with overall colorectal cancer, proximal colon cancer, or rectal cancer. Plasma alkylresorcinols concentrations were associated with colon and distal colon cancer only in Central Europe and Scandinavia (ie, areas where alkylresorcinol levels were higher).ConclusionsHigh concentrations of plasma alkylresorcinols were associated with a lower incidence of distal colon cancer but not with overall colorectal cancer, proximal colon cancer, and rectal cancer.
Keywords: Cancer Research; Oncology; SDG 3 - Good Health and Well-being